Postoperative cervical nodule,s drue to spontaneous thyroid implantation - Perdomo, Roberto; Tchekmedyan, Vartan; Ponaso, Hebe; de los Santos, Julio; Reissenweber, Nelson J; Navarro, Alfredo (Cirugía del Uruguay, 1977)
In three cases of patients that had subtotal thyroidectomies due to simple multinodular goiter, cervical nodules, appeared in the late post-operatory period. Their structure was thyroid and their behaviour functional and evolutive, with general characteristics that defined them as benign, This phenomenon is deemed to be an operatory cell or tissue dissemination, generated during section of parenchyma, susceptible of nodular development when under augmented functional stimuli, especially when little of the thyroid is left. It should be noted that the thesis sustained changes the univoca! concept which consists in interpreting any thyroid growth outside the glandular habitat as carcinomatose metastases and offers a new aspect which should be taken into consideration when these postoperatory nodules appear. These nodules are always located in those sites where dissection has occured: superficial subcutaneous area or deep peri visceral area.